Analisis Sistem Antrian Proses Muat Pakan Ternak Menggunakan Metode Multiple Channel Query System (M/M/S) di PT. JKL - Nabila, Aisyatun; Syaifullah, Hafid (Fakultas Teknik Universitas Tulang Bawang, 2025)
The purpose of this research is to analyze the effectiveness level of the service system in the commercial livestock feed loading process at PT. JKL and to provide improvement suggestions to enhance the performance of the queue system in the livestock feed loading process. The queuing system problem is solved by implementing the queuing theory concept using the multiple channel query system (M/M/S) method. The use of the M/M/S method can analyze the performance of the queuing system in the livestock feed loading process, which provides 6 service servers during the period from 08:30 to 11:30 and 1 queue line. This research uses primary data consisting of the number of vehicle arrivals and the number of vehicles that have been served. From the data processing results, the highest server utilization rate of 40.9% was obtained during the time period between 08:30-09:31 with 3 vehicles in the system. The probability of no vehicles in the system is 8.54% with an average time of vehicles in the system being 5.522 minutes. From these results, suggestions can be made to improve the performance of the queue system by adding forklift operator staff and increasing the loading speed of the contract workers. Keywords: Arrival, Loading Process, Queue, Service